Patients After Mastectomy: The Prevalence of Phantom Breast Syndrome and Its Effect on Depression: Phantom Breast Syndrome after mastectomy - Soomro, Rufina; Jamal, Hamna; Rizwan, Sabbiha; Fatima, Nikhat (Archives of Breast Cancer, 2024)
Background: Phantom breast syndrome (PBS) following mastectomy has been believed to be a complex psychological reaction to mastectomy but studies on PBS are limited. The study aims to determine the prevalence of phantom breast syndrome and the impact of phantom breast syndrome on patients suffering from depression following mastectomy. Methods: A total of 272 women who had undergone mastectomy were interviewed using a structured questionnaire related to phantom breast sensation and depression caused by its effect by using ‘’Hamilton Depression Scale’. SPSS Statistics v27 was used to analyze the data. Results: Out of 272 females, 7.4% of the participants in our study reported having phantom sensations following surgery, 64.7% had Phantom Breast Syndrome,37.5% had mild, 5.1% had moderate, and 0.7% had severe depression according to ‘Hamilton Depression Scale’. Univariate logistic regression revealed that females under 45 have a higher likelihood of developing phantom breast syndrome compared to those over 45 (OR=2.012, p=0.038). Conclusion: Females with depression have a higher likelihood of experiencing phantom breast syndrome compared to females without depression.